A Label-Free Colorimetric Aptasensor for Flavokavain B Detection - Sisi Ke; Ningrui Wang; Xingyu Chen; Jiangwei Tian; Jiwei Li; Boyang Yu (Sensors)
Flavokavain B (FKB), a hepatotoxic chalcone from Piper methysticum (kava), has raised safety concerns due to its role in disrupting redox homeostasis and inducing apoptosis in hepatocytes. Conventional chromatographic methods for FKB detection, while sensitive, are costly and impractical for field applications. In this work, DNA aptamers were selected using the library-immobilized method and high-throughput sequencing. Three families of aptamers were obtained, and the best one named FKB-S showed a dissociation constant (KD) of 280 nM using microscale thermophoresis. To demonstrate its practical utility, a rapid and label-free colorimetric aptasensor was developed based on aptamer-induced gold nanoparticle aggregation. This assay achieved a detection limit of 150 nM (43.46 ng/mL) and provided results within 10 min. Compared to traditional chromatographic methods, the aptasensor offers a simple, cost-effective, and equipment-free approach for on-site FKB detection, making it a promising tool for the quality control and safety monitoring of kava-based products in diverse environments.